Determinants of Capital Structure: An Empirical Study from UK Fims - Chen, Shengming (2013)
During the past several decades, one important and debatable topic in finance field has been the theory of Capital structure. Various theories have been introduced to explore the possible determinants of capital structure. However, as argued by Myers (2001), still no absolute theory of the capital structure choice has been accepted by all. This paper aims to explain why different firms use different levels of debt using the sample which targets all firms in FTSE 350 constituents list which quoted on London Stock Exchange from 1993 to 2012. A panel data for 252 non-financial firms from 10 industries was created. Three different dependent variables computed based on book values have been applied short-term leverage, long-term leverage and total leverage. Additionally, seven potential determinants of capital structure were tested in this paper, including profitability, firm size, growth opportunity, non-debt tax shields, tangibility, volatility, and industry effect. The industry effects on the leverage ratio were investigated by One-way Analysis of Variance (ANOVA); while Multiple Regression was selected to explore the other six determinants.